Arterial hypertension and dental health in children and adolescents (review of literature) - L. R. Kolesnikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
In the review the questions connected with arterial hypertension which is for the first time shown at children and adolescense age are taken up. Violations of neurovegetative and endocrine influences at arterial hypertension are shown by characteristic changes of the central and regional haemodynamics as a result of which metabolic and functional violations in all bodies and systems of an organism are noted, including fabrics of dentofacial system. Violations in system of the microcirculatory bloodstream, in particular in the region of the head and neck, influence on a traffic of fabrics of dentofacial system that promotes more active course of pathological processes in dental tissue and paradentium tissue. When studying incidence of caries of teeth and paradentium diseases by a number of authors the important role of somatic pathology at which there is an increase in prevalence and intensity of dental disorder is established.